Relation of Endothelin-1 and Malondialdehyde with Pre-eclampsia in Pregnant Women - Rhama Hamid Kassar1 , Baedaa Abdulaziz Salman2 , Fatehiya Majeed Noori2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
A case-control study was conducted in Kirkuk city in Kirkuk general hospital from first of March 2018 and to end of September 2018 to evaluate the role of endothelin-1 and malondialdehyde in pathogenesis of pre eclampsia in pregnant women. The study included 30 pregnant women with preeclampsia, patients were defined and divided according to the National High Blood Pressure Education Program Working Group on High Blood Pressure in Pregnancy. A control group of 30 healthy normotensive pregnant females was also included. All comparison groups were matched for mother’s age, parity, and gestational age at the time of enrollment and blood collection. Three ml of blood was collected by vein puncture, blood samples were placed into sterile test tubes and left for 30 minutes at 37 °C then were centrifuged at 3000 rpm for 15 minutes then the clot was removed and the obtained sera were then aspirated using automatic micropipette and transferred into clean test tubes and stored in deep freeze at -20°C for determination of endothelin-1 and malondialdehyde by usingELISA technique. The study showed that the highest mean level of endothelin-1 was found in pregnant women with pre-eclampsia(13.15±2.81 pg/ml) and the lowest mean was in the control group (0.41±0.31 pg/ml). The result was highly significant (P<0.01). The study showed that the highest mean level of MDA was found in pregnant women with pre-eclampsia (6.75±2.94 nmol/ml) and the lowest mean was recorded in the control group (3.85±1.29 nmol/ml). The result was highly significant (P<0.01). The current study showed that the mean age of patients enrolled in the study was 33.5 years, the highest mean of endothelin-1 in HD patients was recorded within the age group 20-29 year of pregnant women with pre-eclampsia. Although the results was non-significant. The study showed positive correlation between endothelin-1 and MDA levels pregnant women with pre-eclampsia. It was concluded that serum endothelin-1 and MDA levels were highly correlated with pregnant women with pre-eclampsia